The Relationship Between Nurse's Caring Behavior and BPJS Patient Satisfaction in the Tulip Inpatient Ward, Bekasi Regency Hospital - Novita Novita (STIKep PPNI Jawa Barat, 2023)
Aims: Caring is critical in increasing patient satisfaction with nursing care. There are nine difficulties, according to the conclusions of a study survey conducted by Indonesia Corruption Watch (ICW) (2015) in five major cities in Indonesia. One of them, 65.4% of bpjs patients, has complained about the nurse's uneducated, inattentive, and arrogant approach. Methods: This study employs an analytic with cross-sectional technique, with the sample consisting of all bpjs patients in Tulip's room at RSUD Kabupaten Bekasi. There were 30 (30,9%) respondents who indicated that nurse caring behavior was good, and 67 (69,1%) respondents who stated that nurse caring behavior was negative out of 97 respondents. There were 27 (27,8%) respondents who were satisfied with nurse care conduct and 70 (72,2%) who were dissatisfied. Results: The study's findings revealed a link between nurse caring conduct and bpjs patient satisfaction in Tulip's room at RSUD Kabupaten Bekasi in March 2019. To all nurses at RSUD Kabupaten Bekasi who work in Tulip's room to develop nurse caring behavior. Conclusion: Nurses should increase their caring conduct during the nursing process by responding to patient complaints, offering support and encouragement, and remaining by the patient's side when necessary. This will boost the nurse's reputation.